Increasing the Effectiveness of Pedagogical Technologies in Education: Psychological Experience of Technological Change Management - Mikhail E. Kosov; Gevorg T. Malashenko; Svetlana V. Frumina; Olga A. Grishina; Olga A. Polyakova; Roman A. Alandarov; Vadim V. Ponkratov; Nataliya S. Shmigol; Svetlana S. Dzusova; Abbas Abd Ali Abbood (Emerging Science Journal, 2023)
This paper investigates the psychology of change management involving a technological change in the educational organization and the administrative and teaching staff. In particular, the paper delineates the staff’s psychological experience regarding the incorporation of pedagogical and educational technologies. In this regard, this article provides theoretical support based on the stimulus-organism-response theory, technological self-efficacy, and technological acceptance model and develops a theoretical model. A quantitative approach was applied to test the model, and research assumptions were drawn from the aforementioned theories. Particularly, disruptive statistics and correlation analysis were employed to test the assumption empirically by collecting data from 500 staff members. The research results highlight that a psychological response serves as the antecedent of the effectiveness of pedagogical and educational technologies, whereby the positive psychological responses (happiness, inspiration, or drive) would increase the effectiveness, while the negative psychological responses (anxiety, stress, and discomfort) would decrease it. This psychological response depends on the perceived self-efficacy and perceived ease of use of the staff, whose lower levels of the two raise the negative psychological response. Generally, to increase the effectiveness of pedagogical and educational technologies, it is essential to effectively manage the psychological well-being of the staff by reducing their negative psychological responses and developing their technological competence (self-efficacy and ability to use with ease). Doi: 10.28991/ESJ-2023-SIED2-05 Full Text: PDF